Automation, Performance and International Competition: Firm-level Comparisons of Process Innovation - Lene Kromann; Anders Sørensen (Copenhagen Business School (CBS), Department of Economics, 2015)
This paper presents new evidence on tradeinduced automation in manufacturing firms using unique data combining a retrospective survey that we have assembled with register data for 2005-2010. In particular, we establish a causal effect where firms that have specialized in product types for which the Chinese exports to the world market has risen sharply invest more in automated capital compared to firms that have specialized in other product types. We also study the relationship between automation and firm performance and find that firms with high increases in scale and scope of automation have faster productivity growth than other firms. Moreover, automation improves the efficiency of all stages of the production process by reducing setup time, run time, and inspection time and increasing uptime and quantity produced per worker. The efficiency improvement varies by type of automation.
hdl:10398/9192
Keywords: D24; L11; L22; O33; 330; automation; productivity; production theory; efficiency